2012
DOI: 10.1016/j.jcrs.2012.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interface reflection in pseudophakic eyes with an additional refractive intraocular lens

Abstract: Findings indicate that implantation of monofocal add-on IOLs will not induce relevant additional disturbing glare compared with conventional pseudophakia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
0
12
0
2
Order By: Relevance
“…However, the R parameter strongly depends on the refractive index difference between two media. 21,22 So, because the refractive index of the aqueous humor remains constant, the higher the refractive index of an IOL, the stronger the interface reflects the light. For instance, one AcrySof IOL (Alcon Laboratories, Inc) with a high refractive index of 1.55 would have a reflectance of 1.1%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the R parameter strongly depends on the refractive index difference between two media. 21,22 So, because the refractive index of the aqueous humor remains constant, the higher the refractive index of an IOL, the stronger the interface reflects the light. For instance, one AcrySof IOL (Alcon Laboratories, Inc) with a high refractive index of 1.55 would have a reflectance of 1.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, one would expect that the visual function of patients with polypseudophakia is not affected by interface reflections because the estimated R coefficient was lower than that of an Acrysof IOL, a commonly implanted, singular IOL with a high refractive index. Schrecker et al 22 studied internal reflections in a two-IOL configuration using a ray-tracing model. They concluded that supplementary IOLs do not produce glare symptoms that could be relevant to a patient's visual function compared with conventional single-lens implantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Previous studies in vitro showed that the optical quality provided by the piggyback system is similar to that provided by a unique IOL, for both monofocal and multifocal IOLs. Schrecker et al 19 compared the surface reflections in a pseudophakic model eye with and without a monofocal add-on IOL and concluded that monofocal add-on IOL implantation did not induce relevant additional disturbing glare compared to conventional pseudophakia. Artigas et al 20 used an artificial eye simulating in vivo conditions of the anterior chamber to measure the modulation transfer function of a piggyback system integrated by a monofocal IOL plus a bifocal IOL of zero power and +3.75 D of addition.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we adopted the Liou-Brennan model eye used in our previous studies [2830] including the decentered pupil. There are various model eyes available for optical simulation which can be customized to individual biometric properties [31].…”
Section: Methodsmentioning
confidence: 99%